Mongolia - Government Financial Sector Reform Program (2000-2010) : Mid-term Review Report - World Bank (Washington, DC, 2013)
In spring 2000 the Government of Mongolia adopted a Long-Term Vision and Medium Term Strategy for Financial Sector Reform and Development in 2000-2010, and implemented the Medium Term Strategy in 2001-2004 under the framework of the Bank s FSAC and ADB s FSPL II. In 2004-2005, a Bank team carried out a series of reviews to take stock of the progress made, and identify the remaining as well as emerging challenges. The reviews enjoyed support and coordination from the Ministry of Finance, the Bank of Mongolia and various financial institutions in Mongolia. The data used for the reviews were mainly those at the end of 2004, some were as recent as June 2005 and beyond. The main findings and recommendations of the reviews are summarized in this report, which serves as an Issues Paper for Bank management and staff working on or interested in Mongolia.